The Effect of Service Quality and Product Variety on Customer Satisfaction at PT Izone Ritel Indonesia - Putri Aulia Chairunisa; Ahmad Soleh; Ida Ayu Made (Utami Publisher, 2026)
This research is motivated by the development of the modern perfume retail industry, which is becoming increasingly competitive, requiring companies to provide a satisfying shopping experience for customers. Although PT Izone Ritel Indonesia has offered a variety of products, initial observations still show consumer complaints regarding delays in service during busy hours and uneven product availability. This phenomenon indicates the need for an in-depth analysis of the factors determining customer satisfaction at the location. The purpose of this research is to analyze and explain the magnitude of the influence of service quality (X1) and product variation (X2) variables on consumer satisfaction (Y), both partially and simultaneously. The research method used is a descriptive quantitative approach with a sample of 56 respondents. Data analysis techniques include classical assumption tests and multiple linear regression analysis. The results of the linear regression analysis The multiple regression produces the equation: Y = −1.185 + 0.186X1 + 0.824X2. The research findings indicate that: (1) Service quality partially has a positive and significant effect on consumer satisfaction, with a t-count value of 2.160 > t-table 2.006 and a significance value of 0.035 < 0.05. (2) Product variety partially has a positive and dominant effect on consumer satisfaction, with a t-count value of 8.389 > t-table 2.006 and a significance value of 0.000 < 0.05. (3) Simultaneously, service quality and product variety have a significant effect on consumer satisfaction, with an F-count value of 1439.00 > F-table 3.17. The coefficient of determination (R Square) obtained is 0.982, which indicates that this model is able to explain 98.2% of the variation in consumer satisfaction.